Our built heritage - Heritage Foundation of Newfoundland and Labrador (Memorial University of Newfoundland. Division of Educational Technology, 1988)
Discussion of Newfoundland and Labrador historical architecture. Includes an overview of Newfoundland and Labrador Heritage Foundation and the heritage home status application process.